ANATOMICAL AND PHYSIOLOGICAL MECHANISMS OF SPEECH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
To know the anatomical and physiological mechanisms of speech, that is, the organization of speech activity in terms of structure and performance, firstly, to imagine the complex mechanism of speech normally, and secondly, a differential approach to the an alysis of speech pathology (disorder); thirdly, it allows correct determination of corrective action paths.